A common variant association study reveals novel susceptibility loci for low HDL‐cholesterol levels in ethnic Arabs. Issue 6 (8th March 2016) - Wakil, S. M.; Ram, R.; Muiya, N. P.; Andres, E.; Mazhar, N.; Hagos, S.; Alshahid, M.; Meyer, B. F.; Morahan, G.; Dzimiri, N.
Abstract : The genetic susceptibility to acquiring low high density lipoprotein‐cholesterol (LHDLC) levels is not completely elucidated yet. In this study, we performed a common variant association study for harboring this trait in ethnic Arabs. We employed the Affymetrix high‐density Axiom Genome‐Wide ASI Array (Asian population) providing a coverage of 598, 000 single nucleotide variations (SNPs) to genotype 5495 individuals in a two‐phase study involving discovery and validation sets of experiments. The rs1800775 [1.31 (1.22–1.42); p = 3.41E‐12] in the CETP gene and rs359027 [1.26 (1.16–1.36); p = 2.55E‐08] in the LMCD1 gene were significantly associated with LHDLC levels. Furthermore, rs3104435 [1.26 (1.15–1.38); p = 1.19E‐06] at the MATN1 locus, rs9835344 [1.16 (1.08–1.26); p = 8.75E‐06] in the CNTN6 gene, rs1559997 [1.3 (1.14–1.47); p = 9.48E‐06] in the SDS gene and rs1670273 [1.2 (1.1–1.31); p = 4.81E‐06] in the DMN/SYNM gene exhibited suggestive association with the disorder. Seven other variants including rs1147169 in the PLCL1 gene, rs10248618 in the DNAH11, rs476155 in the GLIS3, rs7024300 in the ABCA1, intergenic rs10836699, rs11603691 in P2RX3 and rs750134 in CORO1C gene exhibited borderline protective properties. Validation and joint meta‐analysis resulted in rs1800775, rs3104435 and rs359027 retaining their predisposing properties, while rs10836699 and rs11603691 showed protective properties. Our data show several predisposing variants across the genome for LHDLC levels in ethnic Arabs.